Counseling on family planning during ANC service increases the likelihood of postpartum family planning use in Bahir Dar City Administration, Northwest Ethiopia: a prospective follow up study - Tadese Ejigu Tafere; Mesganaw Fanthahun Afework; Alemayehu Worku Yalew (BMC, 2018)
Abstract Background Closely spaced pregnancies within the first year postpartum increases the risk of death for both the mother and baby. Many countries recommend providing pregnant women with post-partum family planning counselling during antenatal care visits. However, data on the extent to which providers utilize these opportunities and the role of family planning counseling during antenatal care in promoting the use of postpartum modern family planning remain limited especially in developing countries. Therefore, this study was aimed at investigating the role of family planning counseling during antenatal care in promoting postpartum modern family planning use within 6 weeks after birth. Methods Nine hundred seventy pregnant women with gestational age ≤ 16 weeks who came for their first Antenatal Care (ANC) visit were enrolled and followed until 6 weeks after delivery. Longitudinal data was collected during consultation with ANC providers using structured observation checklist to assess whether or not the providers counsel pregnant women on post-partum family planning use during their four focused ANC visits. Exit interview was also conducted at 6 weeks after they gave birth when they came to immunize their child to assess whether they were starting to use postpartum modern family planning. Completed data were obtained from 823 women. Generalized Estimating Equation was carried out to identify predictors of postpartum modern family planning use by controlling the cluster effect among women who received ANC services in the same health facility. Results Postpartum modern family planning use within 6 weeks after delivery among the study women was 157(19.1%) with 95%CI (16.4, 21.9); Among 187 pregnant women who were counseled at least once, 72(38.5%) of them used post-partum modern family planning compared to 13.4% of post-partum women who were not counseled at all (p < 0.001). Counseling about postpartum family planning during antenatal care, satisfaction on the antenatal care services women received while they were pregnant, counseling on birth preparedness and complication readiness plan, counseling on breast feeding and post-natal care use were independent predictors for postpartum modern family planning use. Conclusion Less than one in five post-partum women were using postpartum family planning within 6 weeks after birth. Family planning counseling during ANC services had a significant effect on promoting postpartum modern family planning use. Therefore, health providers need to ensure continuity of care through strengthening integration of family planning counseling services during ANC and referral linkages between community and health workers.